2009
DOI: 10.1088/0256-307x/26/1/013102
|View full text |Cite
|
Sign up to set email alerts
|

Finite Space Complete Basis Method: Precision Computation of High-Resolution Spectrum near Ionization Threshold

Abstract: A new method is proposed to describe quantum dynamical processes in finite space by using of a set of discretized complete bases. In this method, the finite space complete basis is obtained by solving the self-consistent field equation with reflecting boundary conditions. Hence, both negative and positive orbital energies can be obtained. Such method can be used in systems which involve dynamics only in the reaction zone, i.e., in a finite space. To illustrate the validity of the method, we present two example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In experiments, the energy resolution is finite, so the measured oscillator strength is actually the oscillator strength density near the threshold, which is smoothly connected to the photoionization spectra [1,55]. In the numerical calculation of the oscillator strength density df l /dE using a basis set, we have shown that it can be calculated by two equivalent methods [55]. One is to calculate the density of state directly by finite difference (including the pseudo states) and using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In experiments, the energy resolution is finite, so the measured oscillator strength is actually the oscillator strength density near the threshold, which is smoothly connected to the photoionization spectra [1,55]. In the numerical calculation of the oscillator strength density df l /dE using a basis set, we have shown that it can be calculated by two equivalent methods [55]. One is to calculate the density of state directly by finite difference (including the pseudo states) and using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…We have used a square grid with a higher concentration of grid points near the nucleus, i.e., r i = i 2 R 0 /N 2 . Furthermore, in the present application of the method, the outer boundary (R 0 ) and the total number of grid points (N ) are chosen to be adaptive for different n and l. Larger R 0 and N are chosen for larger n and l. This kind of numerical-basis set has been used before to calculate atomic photoabsorption spectra for highly excited states as well as continuum states [33,34]. These previous results indicate that the atomic energy levels and dipole transition matrix elements can be well reproduced using the numerical-basis set.…”
Section: A Numerical-basis Statesmentioning
confidence: 99%
“…To this end, we numerically obtain finite-space energy eigenstates for the hydrogen atom in a box [33,34], represent the numericalbasis set on a grid, and propagate the system under the influence of an intense laser pulse. As examples, we calculate the transition probabilities to excited bound states and into the continuum as well as electron momentum spectra.…”
Section: Introductionmentioning
confidence: 99%